Factors affecting career choices of graduates of Bachelor of Library and Information science outside libraries and information centers - Lacsamana, Marlon T. (2008)
Career preparation has long been a major component of university programs and courses since not only do these prepare and support individual students for their future career but also help them set and achieve career and educational goals.